Integrating geriatric assessment in the first line chemotherapy treatment in older patients with metastatic colorectal cancer: Results of a prospective observational cohort study (AVAPLUS). Issue 2 (March 2018) - Decoster, Lore; Kenis, Cindy; Naessens, Benedicte; Houbier, Ghislain; De Man, Marc; Lambrecht, Guy; Monsaert, Els; Moons, Veerle; Vergauwe, Philippe; Prenen, Hans; Van Cutsem, Eric; Wildiers, Hans
Abstract: Objectives : This study aims to investigate the use of chemotherapy with or without bevacizumab in older patients with metastatic colorectal cancer (mCRC) in current daily practice and to identify predictive parameters for treatment-related outcomes. Patients and Methods : This is a Belgian multi-centre, observational cohort study. Patients ≥ 70 years old with mCRC considered suitable for first-line chemotherapy were eligible for inclusion. At baseline geriatric screening and assessment was performed. Treatment choice was at the discretion of the investigator. Treatment duration, Progression Free Survival (PFS) and safety were recorded. Results : Between August 2011 and July 2013, 252 patients with mCRC were included of which 50.8% were treated with bevacizumab. Median treatment duration was 5.5 months and median PFS was 8.9 months. Approximately 50% of patients experienced severe adverse events, most frequently diarrhea. In multivariate analysis, baseline Eastern Cooperative Oncology Group (ECOG)-performance status (PS) was predictive for treatment duration (p = 0.0047), PFS (p < 0.0001) and severe toxicity and baseline nutritional status for PFS (p = 0.0007). In patients with a good ECOG-PS, nutritional status was predictive for PFS. Conclusions : In current daily practice in Belgium, half of older patients with colorectal cancer treated with chemotherapy also receive bevacizumab. Nearly half of older patients presented with severe toxicity during treatment. Baseline nutritional status is a predictive marker for PFS. Patients with a baseline ECOG-PS ≥ 2 have shorter PFS and higher risk of severe toxicity and should therefore be treated with caution.